Lenguaje, poetizar e interpretar. / Language, To Poetize and To Interpret. - GUERRERO LOBO, José Francisco (Utopía y Praxis Latinoamericana)
RESUMEN En el presente trabajo trataremos sobre el sentido de la palabra, el poetizar y el interpretar en Martin Heidegger y Hans-Georg Gadamer. Esta labor es compleja pero abierta al debate de las ideas de dos grandes referentes de la filosofía contemporánea, sus reflexiones filosóficas tematizaron desde configuraciones diferentes, aunque la influencia de la filosofía de Heidegger es preponderante en Gadamer como maestro y alumno. El trabajo está dividido en tres partes, la primera aborda la relación del poetizar en Hölderlin y Heidegger, la segunda se aproxima a la relación hombre, lenguaje y ser en Heidegger y la última parte profundiza en el lenguaje, poetizar e interpretar en Gadamer. ABSTRACT In the present work we will deal with the meaning of the word, poetizing and interpreting in Martin Heidegger and Hans-Georg Gadamer. This work is complex but open to the debate of the ideas of two major referents of contemporary philosophy, his philosophical reflections themed from different configurations, although the influence of Heidegger’s philosophy is predominant in Gadamer as teacher and student. The work is divided into three parts, the first deals with the relationship between poetry in Hölderlin and Heidegger, the second approaches the relationship between man, language and being in Heidegger and the last part delves into language, poetizing and interpreting in Gadamer.